Contribution of imaging modalities to eosinophilic myocarditis diagnosis: a case report. Issue 2 (7th February 2022) - Farhat, Nesrine; Bouhabib, Maya; Joye, Raphael; Vallée, Jean-Paul; Beghetti, Maurice
Abstract: Background: Eosinophilic myocarditis (EM) is a relatively rare form of myocarditis that could progress to restrictive cardiomyopathy and might be fatal if left untreated. Although myocardial biopsy is considered to be the gold standard for the diagnosis of myocarditis, its use in paediatrics remains controversial and not easily applicable in routine practice. Case summary: A 10-year-old girl with no prior medical history presented to the emergency department for fever, odynophagia, and gastrointestinal symptoms despite 48 h of antibiotics (Cefaclor). Physical examination revealed diffuse petechiae and abdominal tenderness but was otherwise unremarkable. Her vital signs were normal. She was found to have hypereosinophilia and increased cardiac markers on laboratory testing. Echocardiography showed diffuse left ventricular (LV) myocardial infiltrates, moderate LV dilatation, and mild systolic dysfunction. Bone marrow biopsy confirmed B cell acute lymphoblastic leukaemia. The diagnosis of EM was made. High doses of steroids and chemotherapy were initiated. Cardiac magnetic resonance imaging (MRI) identified eosinophilic infiltrates and sub-endocardial enhancement strongly suggestive of EM. Left ventricular function was slightly decreased. Intra-ventricular micro-thrombi were suspected, and warfarin was started. The outcome was favourable. Leucocyte and eosinophil counts were normalized within a month. At 6 months, cardiac MRI demonstrated a significant decrease in eosinophilic infiltration and micro-thrombi, normalization of LV function, and of sub-endocardial enhancement. Discussion: This case demonstrates that non-invasive multi-modality imaging along with typical laboratory and clinical findings allow for appropriate diagnosis of EM while avoiding biopsy. It also highlights that an early diagnosis, timely treatment, and rigorous follow-up improve disease progression and outcome.